SPE Annual Technical Conference and Exhibition 2017
DOI: 10.2118/187176-ms
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Surfactant Imbibition and Adsorption for Improving Oil Recovery in the Wolfcamp and Eagle Ford Reservoirs

Abstract: Improving oil recovery from unconventional liquid reservoirs (ULR) is a major challenge and knowledge of recovery mechanisms and interaction of completion fluid additives with the rock is fundamental in tackling the problem. Fracture treatment performance and consequent oil recovery can be improved by adding surfactants to stimulation fluids to promote imbibition by wettability alteration and interfacial tension (IFT) moderate reduction. Also, the extent of surfactant adsorption on the ULR surface during imbib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“…49 Small pores are important in the sorption capability because the capillary effects create a sorption force of the liquid, facilitating the oil’s retention. 4951 The PU C presented a balance between great and small pores, contrasting with PU D-E , and a wider pore distribution (4.9 a 131.4 μm). This distribution tends to influence the sorption capacity.…”
Section: Resultsmentioning
confidence: 97%
“…49 Small pores are important in the sorption capability because the capillary effects create a sorption force of the liquid, facilitating the oil’s retention. 4951 The PU C presented a balance between great and small pores, contrasting with PU D-E , and a wider pore distribution (4.9 a 131.4 μm). This distribution tends to influence the sorption capacity.…”
Section: Resultsmentioning
confidence: 97%
“…The spontaneous imbibition of 4 wt % KI (potassium iodide) into Permian Basin cores resulted in the recovery of 11% OOIP after about 150 h. , Similar experiments with cores from the Wolfcamp formation resulted in the recovery of ∼8% OOIP after about 100 h or ∼2% OOIP after 65 h, and 2% OOIP from an Eagle Ford core after about 50 h . In a thorough study of the characteristics of several ULRs, imbibition of water into short, 2.5 cm diameter Bakken, Wolfcamp, or Eagle Ford cores was slow and required 100–200 h of immersion in order to reach an ultimate oil recovery of only 3–8% OOIP …”
Section: Chemical Eor Using Water In Ulrsmentioning
confidence: 86%
“…266 The authors concluded that the shale could be viewed as a semipermeable membrane that initially promotes the flux of water into the shale at a greater rate than the high salinity formation brine, leading to increased oil recovery due to osmosis. 266,267 The spontaneous imbibition of 4 wt % KI (potassium iodide) into Permian Basin cores resulted in the recovery of 11% OOIP after about 150 h. 247,268 Similar experiments with cores from the Wolfcamp formation resulted in the recovery of ∼8% OOIP after about 100 h 269 or ∼2% OOIP after 65 h, 270 and 2% OOIP from an Eagle Ford core after about 50 h. 269 In a thorough study of the characteristics of several ULRs, imbibition of water into short, 2.5 cm diameter Bakken, Wolfcamp, or Eagle Ford cores was slow and required 100− 200 h of immersion in order to reach an ultimate oil recovery of only 3−8% OOIP. 69 Other tests conducted with Bakken cores noted a higher recovery of oil with LSW than high salinity brine during the long imbibition process; however the cores had very different permeability values: 58% of the oil was recovered using 2 wt % KCl brine in 14 days from a 0.94 mD Bakken core, while it took 23 days to recover 43% of the oil using 24 wt % KCl brine from a 0.001 mD Bakken core.…”
Section: Chemical Eor Using Water In Ulrsmentioning
confidence: 91%
See 1 more Smart Citation
“…Based on Alvarez et al's measurements of contact angles and zeta potentials, the Wolfcamp cores and the Eagle Ford cores demonstrated intermediate wet to oil wet. But, their cores were aged for 4 weeks or 6 months.…”
Section: Wettability Characteristics Of Shale Formationsmentioning
confidence: 65%